Burnout in diabetes and endocrinology specialist registrars across England, Scotland and Wales in the pre-COVID era. Issue 4 (August 2022) - Agha, A.; Basu, A.; Hanif, W.
Abstract: Background: Presence of either emotional exhaustion, depersonalization or lack of personal accomplishment define Burnout Syndrome which may lead to decreased workforce productivity, increased absenteeism, depression and medical errors as well as decreased patient satisfaction. Objective: The aim of this study was to assess the frequency of burnout syndrome among Diabetes Specialist Registrars across England, Scotland and Wales and to identify any self-reported factors which may be contributory to burnout. Methods: Over 430 Diabetes Specialist Registrars were invited to anonymously participate in an electronic survey which used Maslach Burnout Inventory and selfreporting questionnaire to identify burnout and contributory factors. Results: In this pre-pandemic times study, Burnout was identified in 61 (57.5%; n = 106) respondents using Maslach burnout cut-off scores. 45.2% (48/106) participants had scored high in Emotional Exhaustion, while lack of personal accomplishment and depersonalization was seen in 24.5% (26/106) and 21.6% (23/106) of the respondents respectively. The commonest self-reported stressors by participants were "General Internal Medicine workload" 60.4% (64/106) followed by "Lack of specialty training" 36.8% (39/106) and "Lack of audit/research/Continuing Professional Development time" 10.8% (11/106) Conclusion: Burnout syndrome is frequent among the participating Diabetes Specialist Registrars and urgent steps may be required address this problem nationally to ensure that these physicians remain physically and mentally healthy, especially after the pandemic. Highlights: Burnout=Emotional exhaustion, depersonalization & lack of personal accomplishment. Burnout causes decreased productivity & medical errors in healthcare professionals. 50% of Diabetes & Endocrine specialist registrars are found to have Burnout.